Adaptive Reconfiguration of Natural Killer Cells in HIV-1 Infection - Peppa, Dimitra; Pedroza-Pacheco, Isabela; Pellegrino, Pierre; Williams, Ian; Maini, Mala K.; Borrow, Persephone (Frontiers in Immunology, 2018)
Human cytomegalovirus (HCMV) co-infection is highly prevalent within HIV-1 cohorts and is an important co-factor in driving ongoing immune activation, even during effective antiretroviral treatment (ART). HCMV infection has recently been associated with expansion of adaptive-like Natural Killer (NK) cells, which harbor epigenetic alterations that impact on their cellular function and phenotype. The influence of HCMV co-infection on the considerable heterogeneity among NK cells and their functional responses to different stimuli was assessed in a cohort of HIV-1 infected individuals sampled during different stages of infection, compared to healthy subjects stratified according to HCMV serostatus. Our data demonstrate a reshaping of the NK cell pool in HIV-1 infection of HCMV-seropositive individuals, with an accentuated peripheral transition of CD56dim NK cells towards a mature CD57+CD85j+NKG2C+NKG2A- phenotype. Lack of PLZF further distinguishes adaptive NK cells from other NK cells expressing CD57 or NKG2C. PLZF- NK cells from HIV-infected individuals had high expression of CD2, were Siglec-7 negative and exhibited downregulation of key signaling molecules, SYK and FcεRI-γ, overwhelmingly displaying features of adaptive NK cells that correlate with HCMV serum Ab levels. Notably this adaptive-like signature was detected during early HIV-1 infection and persisted during treatment. Adaptive-like NK cell subsets in HIV-1-infected individuals displayed enhanced IFN-γ production following Fc-receptor triggering compared to their conventional NK cell counterparts, and their ability to produce TNF-α and degranulate was preserved. Together these data suggest that HMCV infection/reactivation, a hallmark of HIV-1 infection, plays a role in driving a relative expansion of NK cells with adaptive features during HIV-1 infection. The identification of selective NK subsets with retained effector activity in HIV-1-infected subjects raises the possibility of developing therapeutic strategies that exploit specific NK subpopulations to achieve better HIV-1 control.